Political Corruption: History and Solution - Serirangsan, Prof. Dr. Thirapat (Journal for Developing the Social and Community, 2019)
The article named “Political Corruption: History and Solution” proposes to demonstrate the solution and adjustment. Most importantly, the major factor of a form of corruption appears the corrupt has the misuse of entrusted power for private gain. By doing this, it is essential that a mean of dealing with corruption is building a new political culture along with emphasizing an education including Formal and Non-Formal Education. As for the solution, it could be designed in various ways relying on political issues, regulation, economy and society. A completed setting of political system, firstly, should be verified and efficient counterbalance. Furthermore, potential and moral politicians would be elected for political system. Thirdly, the use of political authority must be monitored and verified effectively. In the same manner, a problem solving of corruption on politics should be proceeded in align with the term of economy and society. First of all, good governance must be applied for business company. In private sector, the business process should take into account for social gap and people inequality excessively as a second concern. Following this, it is necessary that Patronage System should be derogated. As a final point, to attach greater importance to honesty, social responsibility and ethics than exploitation and materialism.